Stabilizing Zn Metal Anodes via Cation/Anion Regulation toward High Energy Density Zn‐Ion Batteries. Issue 8 (4th January 2023) - Zhao, Ran; Yang, Jingjing; Han, Xiaomin; Wang, Yahui; Ni, Qiao; Hu, Zhifan; Wu, Chuan; Bai, Ying
Abstract: Aqueous zinc batteries (AZBs) are promising energy storage devices owing to their high safety, low cost, and environmental friendliness. However, energy density improvement and lifespan prolongation of AZBs are impeded by the poor reversibility of Zn anodes. Instead of focusing on restraining the water activity that has been widely discussed, this work reports a unique strategy to eliminate the side reactions, which is the simultaneous regulation of cation and anion fluxes by microporous material. The as‐synthesized protective layer possesses an excellent sieving ability to repel sulfate infiltration by channel effect and via the electric field, and homogenizes Zn ion flux to achieve a dendrite‐free morphology, which is confirmed by the electrochemical and theoretical investigations. The protected anode exhibits a long lifespan (2400 h), deep Zn plating/stripping, and high current tolerance (100 mA cm −2 ). As a result, the full battery achieves a capacity retention of 76.4% after 7500 cycles, and in the anode‐free configuration, a high energy density of 192.8 Wh kg −1 is observed, which is more than 50 times that of a full battery with a Zn foil anode. By regulating the cations and anions simultaneously, the proposed strategy provides a low‐cost remedy to achieve the practical scale‐up of AZBs. Abstract : A zinc ion exchanged zeolite protective layer is shown to provide three major functions: Zn ion flux is homogenized by the controlled zeolite channels, accompanied with a Zn de‐solvation process; by precisely controlling the sieving ability, the side reactions are eliminated by the absence of sulfate groups; the polarization induced by concentration gradient is weakened. Consequently, an anode‐free battery with high energy density is achieved.